2013
DOI: 10.1089/neu.2013.2960
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Cortical Impact Results in an Extensive Loss of Dendritic Spines that Is Not Mediated by Injury-Induced Amyloid-Beta Accumulation

Abstract: The clinical manifestations that occur after traumatic brain injury (TBI) include a wide range of cognitive, emotional, and behavioral deficits. The loss of excitatory synapses could potentially explain why such diverse symptoms occur after TBI, and a recent preclinical study has demonstrated a loss of dendritic spines, the postsynaptic site of the excitatory synapse, after fluid percussion injury. The objective of this study was to determine if controlled cortical impact (CCI) also resulted in dendritic spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…29 In the present study, we focused our spine counts on layers II/III of the cortex and report that a single mTBI causes a 13% loss of spines in the AO dendrites in young male mice, with a greater spine loss occurring after mTBI on the same dendrites in aged male mice. Combined together, these studies of dendritic spines after TBI show that this is a common phenomenon that occurs in a severe TBI model (controlled cortical impact), 18,30 a moderate TBI model (FPI), 28 and our mild TBI model. Thus, our work and that of others demonstrate that the loss of dendritic spines is an event that occurs after all severities of TBI and may be one of the common acute events that occur after head trauma, even in the absence of neuronal cell death, axonal injury, or inflammation.…”
Section: Rapid But Temporary Synaptic Loss Occurs After a Single Mtbimentioning
confidence: 69%
See 2 more Smart Citations
“…29 In the present study, we focused our spine counts on layers II/III of the cortex and report that a single mTBI causes a 13% loss of spines in the AO dendrites in young male mice, with a greater spine loss occurring after mTBI on the same dendrites in aged male mice. Combined together, these studies of dendritic spines after TBI show that this is a common phenomenon that occurs in a severe TBI model (controlled cortical impact), 18,30 a moderate TBI model (FPI), 28 and our mild TBI model. Thus, our work and that of others demonstrate that the loss of dendritic spines is an event that occurs after all severities of TBI and may be one of the common acute events that occur after head trauma, even in the absence of neuronal cell death, axonal injury, or inflammation.…”
Section: Rapid But Temporary Synaptic Loss Occurs After a Single Mtbimentioning
confidence: 69%
“…18 Bright-field microscopy images of pyramidal neurons in layers II/III of the cortex were captured, and the number of dendritic spines on basal shaft (BS) and apical oblique (AO) dendrites was quantified. BS dendrites project directly off the cell soma, and our counts incorporated dendritic spines along a 20-mm section of the shaft between 30 and 100 mm away from the soma.…”
Section: Golgi Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the last few decades, multiple lines of evidence have shown that disruptions in dendritic spine shape, size, or number invariably accompany various brains disorders, such as schizophrenia [6][7][8][9], Angelman syndrome [10], and Rett syndrome [11][12][13], and may be even be a characteristic feature of traumatic brain injuries [14,15]. What do these various neuropsychiatric and neurodevelopmental diseases share in common?…”
Section: Introductionmentioning
confidence: 99%
“…Blast-injury, among other forms of experimental TBI, causes mild forms of brain damage and diffuse axonal injury. A recent study has shown that controlled cortical impact injury causes local as well as widespread cortical neuronal dendrite degeneration and loss [75]. The mechanisms underlying such events are not well understood, but may, at least in part, result from intracellular transcriptional modulation due to epigenetic changes induced by injury.…”
Section: Epigenetic Modifications Following Central Nervous System Inmentioning
confidence: 99%